A Markov Chain approach to determine the Optimal Performance Period and Bad Definition for Credit Scorecard - CHOY, Murphy (Institutional Knowledge at Singapore Management University, 2011)
Performance period determination and bad definition for credit scorecard has been a mix of fortune for the typical data modeler. The lack of literature on these matters led to aproliferation of approaches and techniques to solve the problems. However, the most commonly accepted approach involves subjective interpretations of the performance period and bad definition as well as being chicken and egg problem. These complications result in poorly developed credit scorecard with minimal benefits to the banks. In this paper, we will be recommending a simple and effective approach to resolve these issues.